Enhancing irrigation utilizing rainwater harvesting in the hilly areas of sylhet: a step toward achieving SDGS - Khondokar Nazia Jarin; Mahi Abrar; Ishraque Bin Khalil; Minarul Islam (PT Pustaka Intelektual Sutajaya, 2026)
The study investigates the feasibility and potential of implementing rainwater harvesting (RWH) systems in the semi-mountainous region of Sylhet, Bangladesh, as a sustainable solution for water resource management. With increasing water scarcity and a heavy reliance on groundwater for irrigation, RWH presents a viable alternative that aligns with multiple Sustainable Development Goals (SDGs). Specifically, it supports SDG 6 (Clean Water and Sanitation) by providing an alternative water source, SDG 2 (Zero Hunger) by enhancing agricultural productivity, and SDG 13 (Climate Action) by promoting water conservation and resilience to climate change. The research examines two small-scale RWH systems in the Sylhet district, assessing their impact on agricultural productivity and groundwater recharge. Findings suggest that RWH can effectively support irrigation during dry periods, transforming previously uncultivated land into productive agricultural areas. By reducing dependency on groundwater, RWH contributes to sustainable water management and helps mitigate the risks of over-extraction. Despite challenges such as high initial expenses, water quality concerns, and space limitations, the study highlights the socio-economic and environmental benefits of RWH. The research ultimately concludes that RWH is a feasible and sustainable alternative to conventional water management methods, effectively addressing water scarcity in Sylhet’s hilly regions while advancing global sustainability efforts.